Mangrove density and delta formation in Segara Anakan Lagoon as an impact of the riverine sedimentation rate - TRI NUR CAHYO; AGUS HARTOKO; MAX RUDOLF MUSKANANFOLA; HAERUDDIN HAERUDDIN; ENDANG HILMI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Cahyo TN, Hartoko A, Muskananfola MR, Haeruddin, Hilmi E. 2024. Mangrove density and delta formation in Segara Anakan Lagoon as an impact of the riverine sedimentation rate. Biodiversitas 25: 1276-1285. Segara Anakan Lagoon (SAL) is in Southwestern of Central Java Province, Indonesia. The Western Part of SAL (WP-SAL) gets its sediment load from the Citanduy River. This research aimed to determine the temporal pattern of the shoreline, water body area, depth, delta formation, and mangrove density at WP-SAL. Shoreline data were extracted from a base map and the satellite imagery. Overlapping analysis of several shorelines and depth maps showed different results in terms of values or patterns. The western part of SAL had silted up and reached more than 85% in 161 years. The sediment accretion impacted the shoreline (between 177 ha yr-1 in 1999-2003), and the average decrease of the water bodies speed was 61 ha yr-1. The Pelawangan Barat waters (PBW) and the main lagoon had a decreasing depth because of the sediment deposits. The sedimentation also greatly impacts mangrove species distribution, clustering and association, and density and mangrove affinity. Mangrove density growth-based and the delta formation were formed and developed following the tidal pattern during floods and ebbs. It can be used to predict the future morphology of WP-SAL. The WP-SAL will be sediment filled and left the waterways channels, it was reached within 13.6 years from 2018, which would be in 2032.